HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN LARI 40 YARD SISWA KELAS V SDN 012 TANJUNG SIMANDOLAK KECAMATAN BENAI - Ederlan Ederlan; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, on the terms of the observations that has been done in SDN 012 Tanjung Simandolak District of Benai seen that the 40 yard dash speed is obtained by the students is still not good, than the target set by KKM teachers, not all students can achieve it. This problem is suspected because of leg muscle explosive students are less than optimal, visible from a distance of inconsistent measures undertaken by students. Therefore, researchers wanted to conduct research on the relationship of leg muscle explosive power to run speed 012 students of SDN Tanjung Simandolak. This type of research is correlational. The sample in this study amounted to 9 people consisting of 5 male and 4 female student student daughter. This study took place in SDN 012 Tanjung Simandolak District of Benai whereas research time in September-October 2016. Data obtained from the standing broad jump test and the test results 40 yard dash. Normality test data using Liliefors with the results of normal distribution of data for L count <L tables. Further data analysis using product moment correlation test and found to calculate the value of r <r Rabel ie 0531 <0707 can thus be concluded that there is no relationship of leg muscle explosive power with 40 yard dash speed of 012 students of SDN Tanjung Simandolak District of Benai.Keywords: explosive power leg muscle, 40 yard, speed running